Preventing GC-Induced Bone Loss in Women with RA - Shuman, Jill (MD Conference Express, 2014)
Glucocorticoids (GCs) are a commonly prescribed treatment for patients with rheumatoid arthritis (RA). However, the long-term use of these agents in postmenopausal women is associated with an increased risk of osteoporosis and fracture. Therefore, the prevention of GC-induced osteoporosis has become an important goal in treating women with RA. This article presents data from the now complete randomized, double-blind phase 4 clinical trial, Efficacy of Monthly Ibandronate in Women With RA and Reduced Bone Mineral Density Receiving Long-Term Steroids [NCT01287533]